1997
DOI: 10.1103/physrevb.56.2208
|View full text |Cite
|
Sign up to set email alerts
|

Quantized conductance in relays

Abstract: We present measurements of the electrical conductance through breaking point contacts in commercial and home-built electromechanical relays under ambient conditions. Inspired by an experiment published by CostaKrämer et al. ͓Surf. Sci. 342, L1144 ͑1995͔͒, we constructed an automated setup, which makes it possible to record the conductance in a breaking contact 25 000 times during 24 h. Quantization of the conductance in units of G 0 ϭ2e 2 /h is shown to be intimately correlated with the choice of contact mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
128
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 43 publications
13
128
0
Order By: Relevance
“…One of the seminal results of mesoscopic physics is that such a wire has a quantized conductance equal to e 2 πh ∼ 77.5 µA/V ∼ (12.9 kΩ) −1 . This was first established using semiconductor structures [3,4,5] at 4 K, but recent experiments on gold contacts have demonstrated it at room temperature [6]. How can a wire have a resistance that is independent of its length?…”
Section: Introductionmentioning
confidence: 99%
“…One of the seminal results of mesoscopic physics is that such a wire has a quantized conductance equal to e 2 πh ∼ 77.5 µA/V ∼ (12.9 kΩ) −1 . This was first established using semiconductor structures [3,4,5] at 4 K, but recent experiments on gold contacts have demonstrated it at room temperature [6]. How can a wire have a resistance that is independent of its length?…”
Section: Introductionmentioning
confidence: 99%
“…Such minute wires can be generated using the scanning tunneling microscope, mechanically controllable break junctions, or other techniques. 1,2) It has been demonstrated in many experiments that the conductances of single-row atomic wires made of monovalent atoms such as Na, 3,4) Cu, [4][5][6] Ag, 5,7) and Au 5,6,8,9) are quantized in the unit of G 0 = 2e 2 =h, where e is the electron charge and h is Planck's constant. Recently, Smit et al 10) observed experimentally that the conductances of monatomic wires of Au, Pt, and Ir oscillate with a period of two atoms as the length of the wire is varied, which is called even-odd oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…As the process of nanowire drawing is by its nature not fully reproducible, conductance histograms are constructed from a large number of conductance traces. In case of gold [3,4] histogram peaks tend to occur around values at integer values of G 0 . The conductance histogram maxima result also from a correlation between the preferred conductance value and the preferred atom arrangement in a single-atom QPC [5].…”
Section: Introductionmentioning
confidence: 98%
“…Its value strongly depends on particular atomic arrangement in a QPC. Typically fabricated by means of a scanning tunneling microscope (STM) [1] and a mechanically controllable break junction (MCBJ) [2], nanowires with QPC have also been produced in relays [3] and between macroscopic wires [4]. In each case, the QPC is achieved by drawing a previously formed nanowire.…”
Section: Introductionmentioning
confidence: 99%